The - Philip, Neil (Oxford University Press, 1996)
The world of children's poetry is as diverse and as miraculous as the human imagination itself, a land where owls and pussy-cats set to sea in beautiful pea-green boats, and tigers burn bright in the forests of the night. It embraces word play, parody, nonsense, lullaby, and elegy, and ranges from brief nursery rhymes to long narratives. It can be utterly silly, but it also recognizes that if children's lives are full of wonder and delight, they are also fraught with worries, disappointments, and moments of sadness. The best children's poets come to terms with grief as well as joy. Now, in The New Oxford Book of Children's Verse, Neil Philip has surveyed and mapped this delightfully protean landscape, in a book that spans some two hundred and fifty years, from Isaac Watts, the first true children's poet, to such classic figures as Lewis Carroll, Edward Lear, and A. A. Milne, to scores of contemporary writers, such as Richard Wilbur, Sandra Cisneros, and Jack Prelutsky